Natural and oil surface slicks as microbial habitats in marine systems: A mini review - Voskuhl, Lisa; Rahlff, Janina (Frontiers in Marine Science, 2022)
Natural and oil surface slicks are widespread phenomena at the air-water interface and represent visible surface films with distinct physicochemical and biological properties compared to non-slick surface films and underlying marine water. Both types of slicks have major functions in nourishing and dispersing surface-dwelling micro- and macroorganisms, contribute to particle generation and carbon cycling, and are known to accumulate pollutants. Despite these functions and the high frequency of slicks in the marine environment, slicks are little understood considering their microbial inhabitants and contributions of these organisms for natural and oil slick establishment, function, and ecology. Our mini review summarizes the current knowledge of microbial life in natural slicks, natural and anthropogenic oil slicks, including the major knowledge gaps and perspectives for future research. Overall, we aim for an increased awareness about the existence of natural slicks, the differentiation between natural and anthropogenic oil slicks and an improved reporting of slick events during sampling of surface film and seawater from the epipelagic zone.